Case Study-Based Marketing Modules on Segmenting, Targeting, and Positioning Strategy Materials for Class X in Vocational High Schools - Istianah, Istianah; Harti, Harti; Sakti, Norida Canda (HK-Publishing, 2022)
AbstractThis development research aims to develop teaching materials for marketing modules based on case studies of BDP class X segmenting, targeting, and positioning strategies. In addition, this study aims to determine the feasibility of the modules based on expert validator assessments, determine the level of practicality, student responses and module effectiveness. which was developed after the trial phase. Thiagarajan's 4-D development model (Define-Design-Develop-Disseminate) was used in the development of this module. This research was tested on 20 students of the BDP skill program class X marketing subjects for segmenting, targeting, and positioning strategies. The results of the development research show that the learning outcomes of experimental class students who use case study-based marketing modules on segmenting, targeting, and positioning strategies are higher than those of the control class.Keywords: Development, Module, and Case Study Method.Â AbstrakPenelitian pengembangan ini bertujuan untuk mengembangkan bahan ajar modul pemasaran berdasarkan studi kasus strategi segmentasi, targeting, dan positioning BDP kelas X. Selain itu, penelitian ini bertujuan untuk mengetahui kelayakan modul berdasarkan penilaian validator ahli, mengetahui tingkat kepraktisan, respon siswa dan keefektifan modul. yang dikembangkan setelah tahap uji coba. Model pengembangan 4-D Thiagarajan (Define-Design-Develop-Disseminate) digunakan dalam pengembangan modul ini. Penelitian ini diujicobakan pada 20 siswa program keahlian BDP kelas X mata pelajaran pemasaran untuk strategi segmentasi, targeting, dan positioning. Hasil penelitian pengembangan menunjukkan bahwa hasil belajar siswa kelas eksperimen yang menggunakan modul pemasaran berbasis studi kasus pada strategi segmentasi, targeting, dan positioning lebih tinggi dibandingkan dengan kelas kontrol.Kata kunci: Pengembangan, Modul, dan Metode Studi Kasus.